2005
DOI: 10.1080/10428190500054426
|View full text |Cite
|
Sign up to set email alerts
|

Regression of lymphomatous skin deposits in a chronic lymphocytic leukemia patient treated with the Toll-like receptor-7/8 agonist, imiquimod

Abstract: The identification of clinically relevant, active immunomodulatory agents is important for developing immunotherapeutic approaches to chronic lymphocytic leukemia (CLL) and other B-cell lymphomas that are not curable with conventional chemotherapy. In this investigation, the imidazoquinoline Toll-like receptor (TLR)-7/8 agonist, imiquimod, was found to mediate the clearance of a lymphomatous skin lesion in a CLL patient. Imidazoquinolines also activated TLR-7/8 signaling pathways, resulting in increased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 3 publications
0
43
0
1
Order By: Relevance
“…Similar observations regarding the effect of CpG oligonucleotides on costimulatory molecule expression have been made by Jahrsdorfer et al [38][39][40] Qualitatively similar findings have been made with imidazoquinolines, which are agonists of TLR-7. 32,35,41 Consistent with signaling through TLR-7, the imidazoquinoline, S28690, activated the NF-kB, JNK and p38 pathways, which were blocked by the IRAK1 inhibitor, AG126, and the endosomal inhibitors, chloroquine and bafilomycin. 32 S28690 invariably increased the expression of the costimulatory molecules that were reported to be increased by CpG oligonucleotides, and also stimulated TNF-a and IL-6 production.…”
Section: Responses Of Cll Cells To Tlr-7 and Tlr-9 Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations regarding the effect of CpG oligonucleotides on costimulatory molecule expression have been made by Jahrsdorfer et al [38][39][40] Qualitatively similar findings have been made with imidazoquinolines, which are agonists of TLR-7. 32,35,41 Consistent with signaling through TLR-7, the imidazoquinoline, S28690, activated the NF-kB, JNK and p38 pathways, which were blocked by the IRAK1 inhibitor, AG126, and the endosomal inhibitors, chloroquine and bafilomycin. 32 S28690 invariably increased the expression of the costimulatory molecules that were reported to be increased by CpG oligonucleotides, and also stimulated TNF-a and IL-6 production.…”
Section: Responses Of Cll Cells To Tlr-7 and Tlr-9 Agonistsmentioning
confidence: 99%
“…Accordingly, topical imiquimod (another imidazoquinoline licensed for the treatment of genital warts and certain skin cancers 16 ) was used to treat a patient with skin involvement by CLL cells and found to clear cutaneous leukemia cells over a period of several weeks. 35 Minimal systemic activity was noted, but the strong local activity suggested that intravenous administration of imidazoquinolines might be useful for treating CLL. Accordingly, a phase I dose-escalation trial of the TLR-7-specific imidazoquinoline, 852A, 70 is ongoing at the Toronto-Sunnybrook Regional Cancer Center, based on the results of a previous phase-I study in solid tumor patients, which suggested a maximum tolerated dose of 1.2 mg/m 2 .…”
Section: Clinical Use Of Tlr Agonists In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…Exciting results have been seen with a TLR-7/8 agonist (AL-DARA) in cutaneous lymphomas (Spaner et al, 2005;Coors et al, 2006). However, recent phase I/II trials of CpG oligonucleotides in lymphoma patients provided no evidence of clinical responses despite increased NK activation (Link et al, 2006).…”
Section: Clinical Results With Tlr Agonists In Hematologic Malignanciesmentioning
confidence: 99%
“…Hyperbaric oxygen may be able to increase intratumoral oxygen tension (Al Waili et al, 2005). The importance of improving tumor oxygenation is possibly shown by the discrepancy between the responses of cutaneous and systemic lymphomas to TLR-agonist therapy (Spaner et al, 2005;Link et al, 2006). While topical administration may yield higher local agonist levels, the greater susceptibility of cutaneous lesions may also be due to proximity to the atmosphere, resulting in higher partial oxygen pressures and greater oxidative phosphorylation in the tumor cells.…”
Section: Strategies To Improve the Efficacy Of Tlr Agonists In Hematomentioning
confidence: 99%